2023
DOI: 10.3390/biology12060856
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus velezensis Strain HN-Q-8 Induced Resistance to Alternaria solani and Stimulated Growth of Potato Plant

Abstract: Bacillus velezensis HN-Q-8, isolated in our previous study, has an antagonistic effect on Alternaria solani. After being pretreated with a fermentation liquid with HN-Q-8 bacterial cell suspensions, the potato leaves inoculated with A. solani displayed smaller lesion areas and less yellowing than the controls. Interestingly, the activity levels of superoxide dismutase, peroxidase, and catalase in potato seedlings were enhanced by the addition of the fermentation liquid with bacterial cells. Additionally, the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…B. velezensis could prevent disease by inducing resistance and promoting the growth of plants [44,46]. For example, it has been reported that the application of B. velezensis controlled crown gall disease in Prunus subhirtella by increasing the activities of PPO and PAL [47].…”
Section: Discussionmentioning
confidence: 99%
“…B. velezensis could prevent disease by inducing resistance and promoting the growth of plants [44,46]. For example, it has been reported that the application of B. velezensis controlled crown gall disease in Prunus subhirtella by increasing the activities of PPO and PAL [47].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, some bacteria and fungi associated with the potato microbiome may demonstrate an antagonistic nature towards diverse pathogenic bacteria, fungi and oomycetes [74][75][76]. In addition, a number of potato symbiotic microorganisms are involved in the defense systems of plants and help them to resist pathogens by triggering the induced systemic resistance or systemic acquired resistance [77][78][79]. Subsequently, infection caused by a specific pathogen makes the potato more exposed to other threats as well.…”
Section: Impact Of Bacterial and Fungal Pathogens On Potato Microbiomementioning
confidence: 99%